TRANSFORMASI FASILITAS PEMBELAJARAN (LITERASI DAN HEALTHY LIFESTYLE) GUNA MENINGKATKAN KUALITAS PENDIDIKAN DI PONDOK PESANTREN ILZAMUL MAJU BAHRIN DESA KIMAK - Prayanti, Baiq Desy Aniska; Endraswari, Putri Mentari; Hartati, Lasmi (Jurnal Abdi Insani, 2025)
This community service activity was carried out with the aim of supporting the improvement of the quality of education at the Ilzamul Maju Bahrin Islamic Boarding School in Kimak Village through the transformation of learning facilities that focus on literacy and a healthy lifestyle. This program was realized through the procurement and socialization of the use of a digital library system and the provision of sports facilities. The results of the activity showed high enthusiasm from teachers and students in trying and using the provided facilities. The digital library system was considered to facilitate access to various reading resources, thereby improving the culture of literacy within the Islamic boarding school environment. Meanwhile, the provided sports facilities encouraged students to be more active in maintaining their health and fitness. The evaluation of the activity, displayed in graphic form, showed the positive response of participants and the Islamic boarding school's readiness to manage this assistance sustainably. Thus, the transformation of learning facilities carried out not only has a short-term impact in the form of improved literacy skills and interest, but also has the potential to encourage transparency, professionalism, and the quality of education at the Islamic boarding school in the long term.